EDUCAÇÃO ESCOLAR QUILOMBOLA NO MARANHÃO: reflexões e particularidades acerca da implantação das diretrizes curriculares estaduais para a qualidade da educação escolar quilombola no sistema estadual de ensino - SOUZA, Virgínia de Fátima Morais Ratiel de (2024)
This paper discusses the implementation of guidelines for quilombola school education in the state of Maranhão, aiming to analyze the implementation process based on the State Curricular Guidelines for the Quality of Quilombola School Education in the State Education System. To this end, a historical review of black slavery in Maranhão was carried out, highlighting the formation of quilombos and the struggles for land regularization in the state. In addition, we problematized the role of the State in relation to racial issues, inequalities and public policies, aiming at racial equality in the country, highlighting affirmative action policies directed at the black and quilombola population. Furthermore, we identified the challenges of the law and guidelines for the implementation of quilombola school education in Maranhão. Regarding the methodology, a bibliographic review and documentary analysis were used with the aim of deepening the theoretical categories investigated. The method of analysis used was historical-dialectical materialism, which is fundamental for the comprehensive understanding of the social reality experienced by the black and quilombola populations. The main results reveal that the formation of Brazilian society, based on black slavery and the capitalist system of production, generated socioeconomic inequalities and perpetuated racism, profoundly affecting ethnic-racial relations in Brazil. It was shown that the implementation of racially-based affirmative action policies, especially in the educational sphere, is crucial for the appreciation of African and Afro-Brazilian history and culture. For the quilombola population, the integration of formal education and traditional knowledge is essential, as it represents not only respect and appreciation of ancestry, but also an important instrument of resistance and the fight against racism.